Effects of Salt Concentrations on the Functional Properties of Some Legume Flours - Ogungbenle, Henry Niyi (Pakistan Journal of Nutrition, 2008)
The effect of various salt concentrations on the functional properties of gourd seed, white melon, yellow melon and bulma cotton seed was investigated. The studies on the effect of salts commonly used in food industries such as NaCl, KCl, Na2SO4, K2SO4 and CH3CO2Na on the functional properties of the sample suggested that water absorptivity, emulsification, foamability and gelation were affected by the salts and that these effects were functions of the types of salt considered and their various concentrations. The data generated showed that salts may be used at appropriate concentrations to enhance or inhibit the functionalities of the flours.